2018
DOI: 10.1002/ece3.4778
|View full text |Cite
|
Sign up to set email alerts
|

Near‐complete genome assembly and annotation of the yellow drum (Nibea albiflora) provide insights into population and evolutionary characteristics of this species

Abstract: Yellow drum (Nibea albiflora) is an important fish species in capture fishery and aquaculture in East Asia. We herein report the first and near‐complete genome assembly of an ultra‐homologous gynogenic female yellow drum using Illumina short sequencing reads. In summary, a total of 154.2 Gb of raw reads were generated via whole‐genome sequencing and were assembled to 565.3 Mb genome with a contig N50 size of 50.3 kb and scaffold N50 size of 2.2 Mb (BUSCO completeness of 97.7%), accounting for 97.3%–98.6% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Among TEs, the largest contribution of sequence comes from DNA transposons (4.27–5.31%), followed by LINEs (1.88–1.99%%), and LTR elements (1.01–1.33%) (Table 2 ). These figures are broadly similar to those reported for the yellow drum Nibea albiflora [ 11 ], another perciform fish with a similarly low TE content.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Among TEs, the largest contribution of sequence comes from DNA transposons (4.27–5.31%), followed by LINEs (1.88–1.99%%), and LTR elements (1.01–1.33%) (Table 2 ). These figures are broadly similar to those reported for the yellow drum Nibea albiflora [ 11 ], another perciform fish with a similarly low TE content.…”
Section: Resultssupporting
confidence: 88%
“…At the upper end of the spectrum for perciform fish, the pikeperch (Percidae: Sander lucioperca ) has an estimated genome size of 1014 Mb, and an assembly genome size of ~ 900 Mb [ 32 ], and the red sea bream (Sparidae: Pagrus major ) has an estimated genome size of ~ 806 Mb, and an assembly genome size of 829.3 Mb. Meanwhile, at the lower end of the spectrum, the yellow drum (Sciaenidae: Nibea albiflora ) has an estimated genome of 573–581 Mb and an assembly genome size of 596 Mb [ 11 ], and the Chinese sillago (Sillaginidae: Sillago sinica ) has an estimated genome size of ~ 524 Mb, and an assembly genome size of just 534 Mb [ 33 ]. Comparison of various percid fish genomes showed that E. tetradactylum possesses the largest number of protein-coding genes, but the smallest average protein size, which may contribute to its small overall genome size, despite its large number of genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the decrease in sequencing costs, it is easy to genotype genome-wide SNPs using whole-genome sequencing or genotyping-by-sequencing (GBS) (Rustagi et al 2017). The genome of yellow drum is only approximately 565 Mb (Han et al 2019), which is a great advantage for use with sequencing techniques to obtain a large number of genome-wide SNPs and favors the application of genomic selection to the yellow drum genetic breeding program. Genome-wide association study (GWAS) analysis is an efficient approach for screening trait-related markers or genes (Wang et al 2019; Yu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in the Supernova input report estimation (Table 1) of mean distance between heterozygous SNPs in the whole genome of 197 bp. This high SNP heterozygosity (1/206), observed solely in the comparison of the phased alleles, is higher than the average nucleotide diversity of the previously reported marine fish of wild populations: 1/390 in yellow drum [43], 1/309 in herring [44], 1/435 in coelacanth [45], 1/500 in cod [46], and 1/700 in stickleback [47].…”
Section: Data Descriptionmentioning
confidence: 61%